Paradigmskiftets primat - Bränström Öhman, Annelie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
Fundamental changes in our assumptions of the world is seldom recognized in broad daylight. Or, to put it with a famous quote from T S Eliot's poem "The hollow men" (1925): "This is the way the world ends/Not with a bang but a whimper". The same pattern can be recognized in both the rhetorical and theoretical performance of a paradigm shift in academia. In this article it is argued that the silence surrounding the integration of the so called "Excellence"-concept in Swedish universities, can serve as an illustrative example of how the "already-there"-ness of paradigm shifts shuts up a critical debate before it even has been articulated. This is explained by the fact that we usually notice a paradigm shift not by its arrival but by its presence, because we are academically trained to think of change and development in terms of conflicting claims. According to this logic, old assumptions of, for instance, knowledge are predestined to be conquered by new and stronger ideas. As it is pointed out in the end of the article, the hidden gender agenda of this thought pattern yet passes embarrassingly unseen.